PENGGUNAAN MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN (POE) DALAM MENINGKATAN HASIL BELAJAR PESERTA DIDIK - Amahoru, M; Unwakoly, S; Manoppo, Y (Atom : Jurnal Riset Mahasiswa, 2023)
Research has been conducted to determine student learning outcomes on acid, base, and salt materials using the Predict Observe Explain (POE) learning model to improve student learning outcomes for class VII SMP Negeri 19 Ambon. The sample of this research was the students of class VII5, which amounted to 27 students. This research is descriptive and quantitative, with data collection techniques in the form of tests and observations. Instruments were used as initial tests, LKPD, final tests, and non-tests in the form of affective and psychomotor observation sheets. The results showed that in the initial test, all students had not reached the KKM, and student learning outcomes in the form of a final test showed eight students (29.96%) were in excellent qualifications, good qualifications 12 students (44.44%) and enough qualifications for seven students (25,6%). Then for the results of the N-gain analysis, 21 students who achieved (77.78%) were in the high category, six students who achieved (22.22%) were in the medium category, and none were in a low category. Thus, using the Predict Observe Explain (POE) learning model can improve the learning outcomes of class VII students of SMP Negeri 19 Ambon on acids, bases, and salts